A case of chronic Budd-Chiari syndrome - Zheltova, O I; Batorov, E V; Starostina, N M (Terapevtic̆eskii arhiv, 2010)
The Budd-Chiari syndrome is a rare disease associated with occlusion of the hepatic vein by a tumor or a thrombus. It develops due to progressive narrowing or occlusion of the hepatic veins and may occasionally proceed through the chronic disease within months, rarely years as individual recurrences, with pains, enlarged liver, and mild jaundice. These patients generally have partial hepatic vein occlusion. The paper describes a long (more than 20 years) course of the Budd-Chiari syndrome in which only a special angiographic study could verify the presumptive diagnosis and reveal the cause of evolving liver cirrhosis.